Youth and agriculture : key challenges and concrete solutions (FAO RomeIT, 2014)
Shows how tailor-made educational programmes can provide rural youth with the skills and insights needed to engage in farmingand adopt environmentally friendly production methods. Posits that with some additional effort, through farmer organisations and improved infrastructure, young farmers can connect to markets to sell their often higher-value food.
Keywords: YOUTH